A thematic analysis of bereaved adults' meaning-making experience of loss through playing video games - Eum, Karam; Doh, Young Yim (Frontiers in Psychology, 2023)
Introduction Recalling personal memories on the loss and deriving new meanings from them is deemed necessary for adapting to bereavement. Recent studies suggest that games can afford players meaningful experiences that can support players through stressful life events, but its potential on the meaning-making of loss has not been much explored. To address this gap, we investigated the bereaved players' experiences of playing commercial video games that elicited their personal memories of loss and what meanings they derived from those experiences. Method Twelve adult players with bereavement experiences (six male, six female, age range: 20-31) played two video games (Bear's Restaurant and Spiritfarer). Their experiences during and after gameplay were tracked via play diaries and in-depth interviews. Data was analyzed using thematic analysis method. Results We discovered seven themes on the meanings that players made from their gameplay experience: “Recalling memories”, “Avoiding engagement with the pain”, “Recognizing positive emotions”, “Acknowledging the deceased's perspective”, “Reviewing the meaning of loss”, “Planning a better future”, and “Fulfilling a wish”. Our findings indicate that bereaved players recalled and related their autobiographical memories to their in-game experiences. Furthermore, they derived new meanings on both the loss and their post-loss life after playing video games. Discussion We discuss how video games can provide a unique meaning-making experience to bereaved players by affording them an agency to actively reconstruct their narrative of loss and facilitating the sharing of grief.